2008
DOI: 10.3354/dao01912
|View full text |Cite
|
Sign up to set email alerts
|

Myxidium scripta n. sp. identified in urinary and biliary tract of Louisiana-farmed red-eared slider turtles Trachemys scripta elegans

Abstract: During a necropsy investigation of a mortality event occurring at a turtle farm in Assumption Parish, Louisiana, spores of a myxozoan were identified in the renal tubules in 3 of 6, the gall bladder lumen in 2 of 6, and the bile ductule in 1 of 6 red eared slider turtles Trachemys scripta elegans. In total, myxozoa were identified in 4 of 6 turtles. In 1 turtle, renal tubules contained numerous mature spores, had epithelial hyperplasia, granulomatous transformation, compression of adjacent tubules and intersti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…However, Myxidium scripta and M. hardella , infecting freshwater turtles, are also reported from renal tubules as well as from the bile ducts and gall bladder [35,36]. This may be due to these reports being from systemic infections, as in both cases severe pathologies and mortalities had occurred, and it is possible that the hepatic biliary system is the initial site of infection with other organs only becoming infected during the advanced stages of infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, Myxidium scripta and M. hardella , infecting freshwater turtles, are also reported from renal tubules as well as from the bile ducts and gall bladder [35,36]. This may be due to these reports being from systemic infections, as in both cases severe pathologies and mortalities had occurred, and it is possible that the hepatic biliary system is the initial site of infection with other organs only becoming infected during the advanced stages of infection.…”
Section: Discussionmentioning
confidence: 99%
“…These myxozoans are primarily fish parasites usually infecting the gall-bladder of the hosts. However, several species have been described from amphibians (Lutz, 1889;Jirků et al, 2006;Gray, 1992;Sarkar, 1982a;Carini, 1932;Kudo & Sprague, 1940;Delvinquier et al, 1992) and reptiles (Garner et al, 2005;Roberts et al, 2008;Johnson, 1969;Kudo, 1920;Laveran, 1897) -for a review see Eiras (2005), and recently a species was described infecting birds .…”
Section: Introductionmentioning
confidence: 97%
“…The species have generally been described as infecting aquatic animals, especially fish, however many recent studies have reported the occurrence of myxozoans infecting mollusks [3], amphibians [4], [5], reptiles [6], [7], birds [8] and mammals [9]. As demonstrated firstly by Wolf and Markiw [10], it has been also proven that several other myxozoan species require an alternate invertebrate host (usually an annelid) to complete the life cycle [11][13].…”
Section: Introductionmentioning
confidence: 99%